Question and Answers Forum

All Questions      Topic List

Arithmetic Questions

Previous in All Question      Next in All Question      

Previous in Arithmetic      Next in Arithmetic      

Question Number 74819 by Raxreedoroid last updated on 01/Dec/19

Expand Σ  ((4n−1)/3)+(2/3)Σ_(k=1) ^(n−1) cos(120k)

ExpandΣ4n13+23n1k=1cos(120k)

Commented by mathmax by abdo last updated on 01/Dec/19

let S_n =((4n−1)/3) +(2/3)Σ_(k=1) ^(n−1)  cos(120k)   first let find   W_n (α) =Σ_(k=1) ^(n−1)  cos(αk) ⇒W_n (α)=Re(Σ_(k=1) ^(n−1)  e^(iαk) )  and Σ_(k=1) ^(n−1)  e^(iαk)  =Σ_(k=0) ^(n−1) (e^(iα) )^k −1 =((1−e^(inα) )/(1−e^(iα) )) −1  =((1−cos(nα)−isin(nα))/(1−cos(α)−isin(α))) −1  =((2sin^2 (((nα)/2))−2isin(((nα)/2))cos(((nα)/2)))/(2sin^2 ((α/2))−2i sin((α/2))cos((α/2))))−1 =((−isin(((nα)/2))e^((inα)/2) )/(−isin((α/2))e^((iα)/2) ))−1  =((sin(((nα)/2)))/(sin((α/2))))e^(i(((n−1)α)/2))) −1  ⇒W_n (α)=((sin(((nα)/2))cos((((n−1)α)/2)))/(sin((α/2))))−1  Σ_(k=1) ^(n−1)  cos(120k) =W_n (120) =((sin(60n)cos(60(n−1))/(sin(60)))−1 ⇒  S_n =((4n−1)/3)+(2/3){((sin(60n)cos(60n−60))/(sin(60)))−1}

letSn=4n13+23k=1n1cos(120k)firstletfindWn(α)=k=1n1cos(αk)Wn(α)=Re(k=1n1eiαk)andk=1n1eiαk=k=0n1(eiα)k1=1einα1eiα1=1cos(nα)isin(nα)1cos(α)isin(α)1=2sin2(nα2)2isin(nα2)cos(nα2)2sin2(α2)2isin(α2)cos(α2)1=isin(nα2)einα2isin(α2)eiα21=sin(nα2)sin(α2)ei(n1)α2)1Wn(α)=sin(nα2)cos((n1)α2)sin(α2)1k=1n1cos(120k)=Wn(120)=sin(60n)cos(60(n1)sin(60)1Sn=4n13+23{sin(60n)cos(60n60)sin(60)1}

Commented by mathmax by abdo last updated on 01/Dec/19

i considered that 120 mean 120 radian  if the mesure is in degre  α =((120π)/(180)) =((2×6π)/(3×6π)) =((2π)/3)  in this case we get  S_n =((4n−1)/3) +(2/3){ ((sin(((nπ)/3))cos(((n−1)/3)π))/(sin((π/3))))−1}

iconsideredthat120mean120radianifthemesureisindegreα=120π180=2×6π3×6π=2π3inthiscasewegetSn=4n13+23{sin(nπ3)cos(n13π)sin(π3)1}

Answered by mind is power last updated on 01/Dec/19

cos(kx)=Re(e^(ikx) )  Σ_(k=1) ^(n−1) e^(ikx) =e^(ix) .(((1−(e^(ix) )^(n−1) )/(1−e^(ix) ))  =(e^(ix(((n+1)/2))) /e^(i(x/2)) ).((sin(((n−1)/2))x)/(sin((x/2)))),Re(Σe^(ikx) )=Σcos(kx)=cos(((nx)/2)).((sin(((n−1)/2)x))/(sin((x/2))))  forx=((2π)/3)  S=cos(((nπ)/3)).((sin((n−1)(π/3)))/(sin((π/3))))  =(2/(√3)).cos(((nπ)/3))sin(((n−1)/3)π)  sin(((n−1)/3)π)=sin(((nπ)/3))(1/2)−((√3)/2)cos(n(π/3))  cos(((nπ)/3)),sin(((nπ)/3))  (e^(i(π/3)) )^n =f(n)  We worck modd 6  n≡0(6),f(n)=1,n≡1(6),f(n)=(1/2)+((i(√3))/2)  n≡2(6),f(n)=−(1/2)+((i(√3))/2)  n≡3(6),f(n)=−1  n≡4(6),f(n)=−(1/2)−((i(√3))/2)  n≡5(6),f(n)=(1/2)−i((√3)/2)  S=((cos(((nπ)/3))sin(((nπ)/3)))/(√3))−cos^2 (((nπ)/3))  put different case n modd 6 get close forme add ((4n−1)/3)  ge final answer

cos(kx)=Re(eikx)n1k=1eikx=eix.(1(eix)n11eix=eix(n+12)eix2.sin(n12)xsin(x2),Re(Σeikx)=Σcos(kx)=cos(nx2).sin(n12x)sin(x2)forx=2π3S=cos(nπ3).sin((n1)π3)sin(π3)=23.cos(nπ3)sin(n13π)sin(n13π)=sin(nπ3)1232cos(nπ3)cos(nπ3),sin(nπ3)(eiπ3)n=f(n)Weworckmodd6n0(6),f(n)=1,n1(6),f(n)=12+i32n2(6),f(n)=12+i32n3(6),f(n)=1n4(6),f(n)=12i32n5(6),f(n)=12i32S=cos(nπ3)sin(nπ3)3cos2(nπ3)putdifferentcasenmodd6getcloseformeadd4n13gefinalanswer

Commented by Raxreedoroid last updated on 01/Dec/19

I dont know why but I got a different solution  I got  ((2(√3)cos(((2π)/3)n−((5π)/6))+12x−6)/9)

IdontknowwhybutIgotadifferentsolutionIgot23cos(2π3n5π6)+12x69

Terms of Service

Privacy Policy

Contact: info@tinkutara.com